Effect of Doping for Barium M-Hexaferrite Material Composition on Microwave Absorption Effect (A Systematic Review) - Susilawati; Teguh Ardianto; Aris Doyan; Nina Nisrina; Wan Yusmawati Binti Wan Yusoff; Jaswadi (Postgraduate, University of Mataram, 2025)
Research in the field of materials, especially the magnetic properties of materials, continues to increase. This is because Indonesia is one of the countries whose technological developments are developing very rapidly, where the amount of energy use is on a large scale, so that human needs for renewable energy sources must be met properly. This research aims to identify and analyze research trends of doping for barium m-hexaferrite material composition. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2016-2025 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research doping for barium m-hexaferrite material composition that is widely cited. The data analysis method uses bibliometric analysis assisted by VOS viewer software. The results of the analysis show that research trend indexed by Google Scholar from 2016 to 2025 has experienced ups and down. There are many documents in the form of articles, chapters, preprints, monograph, proceeding and edited books that discuss research about doping for barium m-hexaferrite material composition. Key words that are often used in research about it are synthesis, characterization, permanent magnet, etc.